Unveiling adulteration in acacia honey originated from Tuzla area by the Pivot Profile technique - Pestorić Mladenka V.; Tomić Jelena M.; Mandra Muamer J.; Hodžić Sanel S.; Maravić Nikola R.; Škrobot Dubravka J.; Ubiparip Samek Dragana N. (Food and Feed Research, 2025)
This research aimed to examine the applicability of the Pivot Profile (PP) technique in detecting adulteration in acacia honey from the Tuzla region, Bosnia and Herzegovina (B&H). The PP technique captured the relative meaning of descriptors and gathered free descriptions of differences between a target product and a pivot product (PVT), which served as a standard. Four pairs of samples were evaluated: original acacia honey (PVT) versus honey samples adulterated with 20%, 40%, 60%, and 80% fructose-glucose syrup. The sensory assessment involved 72 participants (25 women and 47 men), all acacia honey producers aged from 20 to 55 years of age. The chi-square test (ch² = 3032.37, p < 0.001) revealed significant statistical differences among values, indicating that the consumer panel effectively distinguished the samples. The chi-square test per cell was used to explore variation within the data matrix, identifying descriptors significantly differing from PVT in citation frequency. A total of 48 sensory attributes were generated (5 for appearance, 14 for odours, 4 for basic tastes, 3 for aftertastes, 16 for flavours, 2 for trigeminal effects, and 4 for texture). Correspondence Analysis (CA) was employed to visually represent sensory changes in honey samples based on adulteration levels, illustrating consumer perception of samples and attributes. CA effectively explained nearly 60% of the variability observed across the initial two dimensions, thus emphasizing the connection between sensory alterations and consumer perception. The results revealed a reduction in aroma and appearance attributes, along with occurrences of sensory defects such as off-flavours, unpleasant trigeminal effects, and altered viscosity properties. PP technique provided detailed information about each sample, assessing similarities and differences compared to PVT in a single session using multivariate techniques, contrasting with traditional trained or expert assessments. The PP technique appears promising for further exploration in vocabulary use and data analysis, not only for other honey types but also for various food products susceptible to adulteration.